Oviposition of the Andean weevil, Premnotrypes vorax (Hustache) (Coleoptera: Curculionidae) - VALENCIA-V., LUIS; BOHÓRQUEZ, CARLOS (Revista Colombiana de Entomología, 1994)
The oviposition of the Andean weevil,Premnotrypes vorax (Hustache), has not been orderly researched in the past. The published observations were made while the life cycle of the insect was studied. In this paper, plastic containers with a layer of vegetal soil were used. In each container five couples of adults of the insect were placed together with four pieces of barley stems as an oviposition substrate. Four treatments were investigated 1) potato leaves of the Criolla cv. (Solanum phureja); 2) cut disks from tubers of the Criolla cv.; 3) leaves of the weed Rumex sp.; and 4) an absolute control in which the adults did not have food. Evaluations were made weekly, changing the pieces of barley stems and counting the number of eggs laid per container. Each treatment had five replications and the experiment was run for four weeks. The results show that the potato plant, both leaves or tubers, stimulated the P. vorax oviposition. On the other hand, the leaves of Rumex sp. and the absolute control did not induce oviposition.